Analysis of Solar Powered Micro-Inverter Grid Connected System for a Cellular Communication Network - Alumona , TL; Oranugo, CO; Eze , CE; Onyeyili , TI (International Journal of Computer Sciences and Engineering, 2019)
The power consumption of wireless access networks has become a major economic and environmental issue. Providing dedicated low cost power supply to cell sites located in the rural and sub-urban areas of developing countries is most challenging, as most of the rural areas are not connected to the electricity grid and, even though they are connected, the availability of the supply is very limited to provide uninterrupted power supply. This paper developed a Solar Powered Micro-Inverter Grid connected System as an alternative solution to the problems encountered with power supply in cell sites. The configuration of the Solar Powered Micro-Inverter Grid connected System examined in this paper include a Solar Power System, Diesel generator, battery bank and Grid. Analysis of results shows that, after fifteen (15) years of operation, the reliability figures of solar power system is much higher than 80%. But that of the generator is approaching 15%. Comparing these figures with the general bath tub, it can be seen that the reliability of generator after five years of operation degrades by 60%. It was also found that, the developed Solar Powered Micro-Inverter Grid connected System has very high reliability figures with the Mean Time Before Failure (MBTF) of about twenty three (25) years before complete failure as compared to eight (8) years for generator system.